Study of Bisphosphonates Efficacy in the Treatment of Gonarthrosis - معروف روان; كاسر الدو; عبد الرزاق حسن (Latakia University Journal -Medical Sciences Series, 2022)
Background: Osteoarthritis (OA) is the most common joint diseases. There are currently no treatments that delay or stop the progression of osteoarthritis. However, in general, bisphosphonates may show some positive effects on structure and symptoms due to their ability to modulate the metabolism of osteoclasts and osteoblasts in the subchondral bone and to inhibit synovial inflammatory processes. The aim of the study: to study the efficacy of bisphosphonates in patients with osteoarthritis of the knee joint both radiologically and clinically. Methods: A randomized clinical pilot study was conducted that included 97 patients of primary osteoarthritis of the knee joint who attended the Clinic and Department of Musculoskeletal Diseases at Tishreen University Hospital in Lattakia in the period between 2020-2021 who fulfilled the inclusion criteria in the study. Radiographs of the knee joints were performed. The Kellgren and Lawrence Index (KL) was evaluated, including the Joint Space Width (JSW) measure, and the clinical assessment was done using the Western Ontario and MacMaster Univerities Index (WOMAC) and Visual Analog Scale (VAS). The lengths and weights of all patients were also registered and Body Mass Index (BMI) was calculated., at the first visit, then patients were randomly divided into three groups according to the drug administered (alendronate 70 mg weekly, alendronate 35 mg weekly, paracetamol 2g daily ) and then the variables were re-evaluated one year later. Results: Bisphosphonates showed clinical improvement in the (WOMAC) Index for pain in patients with osteoarthritis of the knee joint, it also showed a benefit in slowing the progression of the disease radiogically. Conclusion: According to the results of our study, bisphosphonates could be used in patients with osteoarthritis to relieve pain and slow the progression of the disease radiogically, but we need more studies with a larger number of patients and for a longer period to know the effect of bisphosphonates on the structure of the degenerative joint